Intraoperative MRI-guided Resection in Pediatric Brain Tumor Surgery: A Meta-analysis of Extent of Resection and Safety Outcomes - Wach, Johannes; Banat, Mohammad; Borger, Valeri; Vatter, Hartmut; Haberl, Hannes; Sarikaya-Seiwert, Sevgi (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2020)
Background The objective of this meta-analysis was to analyze the impact of intraoperative magnetic resonance imaging (iMRI) on pediatric brain tumor surgery with regard to the frequency of histopathologic entities, additional resections secondary to iMRI, rate of gross total resections (GTR) in glioma surgery, extent of resection (EoR) in supra- and infratentorial compartment, surgical site infections (SSIs), and neurologic outcome after surgery.Methods MEDLINE/PubMed Service was searched for the terms “intraoperative MRI,” “pediatric,” “brain,” “tumor,” “glioma,” and “surgery.” The review produced 126 potential publications; 11 fulfilled the inclusion criteria, including 584 patients treated with iMRI-guided resections. Studies reporting about patients <18 years, setup of iMRI, surgical workflow, and extent of resection of iMRI-guided glioma resections were included.Results IMRI-guided surgery is mainly used for pediatric low-grade gliomas. The mean rate of GTR in low- and high-grade gliomas was 78.5% (207/254; 95% confidence interval [CI]: 64.6–89.7, p < 0.001). The mean rate of GTR in iMRI-assisted low-grade glioma surgery was 74.3% (35/47; 95% CI: 61.1–85.5, p = 0.759). The rate of SSI in surgery assisted by iMRI was 1.6% (6/482; 95% CI: 0.7–2.9). New onset of transient postoperative neurologic deficits were observed in 37 (33.0%) of 112 patients.Conclusion IMRI-guided surgery seems to improve the EoR in pediatric glioma surgery. The rate of SSI and the frequency of new neurologic deficits after IMRI-guided surgery are within the normal range of pediatric neuro-oncologic surgery.
Keywords: pediatric brain tumor; extent of resection; glioma; intraoperative MRI; surgical site infection